A Study of Blood Pressure Profile in School Going Adolescents of District Jaipur (Rajasthan) - Swarnkar Madhusudan; Vaseem N Baig; Ashok K Bhardwaj; Monika Rathore; Amita Kasyap (Medsci Publications, 2012)
Background & Objectives: The studies on Blood Pressure in school age population are deficient in this part of the country (Rajasthan). The present study was conducted to evaluate the Blood Pressure profile of school going adolescents in the age group of 11-19 years of Jaipur (Rajasthan) and to compare rural and urban adolescents. Methods: The study was carried out among 4237 students of class 6th-12th of Dist. Jaipur (Raj.) in the age group of 11 to 19 years. Height and Weight were measured using standardized equipment and procedure. The blood pressure was measured using mercury sphygmomanometer. Results: The overall mean Systolic Blood Pressure (SBP) and mean Diastolic Blood Pressure (DBP) were 109.2 mm Hg (range 72 to 161) and 72.4 mm Hg (range 39 to 110) respectively. Mean SBP and DBP among the male students were 108.8 mm Hg and 72.6 mm Hg. The females had mean SBP and mean DBP of 109.7 mm Hg and 72.0 mm Hg, respectively. Both mean SBP and DBP were high in rural population than that of urban, among all age groups in both genders (P=0.01). Conclusion: Mean blood pressure was found higher among females than that of males and in rural students than that of urban.